2016
DOI: 10.1017/s0031182016002298
|View full text |Cite
|
Sign up to set email alerts
|

Haemosporida prevalence and diversity are similar in endangered wild whooping cranes (Grus americana) and sympatric sandhill cranes (Grus canadensis)

Abstract: SUMMARYThe population growth of endangered whooping cranes (Grus americana) is not consistent with species recovery goals, and the impact of parasite infection on whooping crane populations is largely unknown. Disease ecology and epidemiology research of endangered species is often hindered by limited ability to conduct invasive sampling on the target taxa. Accordingly, we hypothesized that sandhill cranes (Grus canadensis) would be a useful surrogate species to investigate the health impacts of Haemosporida i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Lineage pGRW09 was also reported from the European bee-eater Merops apiaster in Portugal and Germany, confirming the presence of a P. circumflexumrelated lineage in birds of the order Coraciiformes [86]. Lineage pSW5, which was also linked to P. circumflexum [130], was found mainly in Anseriformes and Gruiformes in the USA and Japan [59,131,132].…”
Section: Plasmodium Parasites Of Accipitriform Raptorssupporting
confidence: 56%
“…Lineage pGRW09 was also reported from the European bee-eater Merops apiaster in Portugal and Germany, confirming the presence of a P. circumflexumrelated lineage in birds of the order Coraciiformes [86]. Lineage pSW5, which was also linked to P. circumflexum [130], was found mainly in Anseriformes and Gruiformes in the USA and Japan [59,131,132].…”
Section: Plasmodium Parasites Of Accipitriform Raptorssupporting
confidence: 56%
“…Wetland loss has likely resulted in increasing concentrations of Whooping Cranes in aquatic habitats, which pose significant disease risks including avian cholera, botulism, tuberculosis, and coccidiosis (Windingstad, 1988;Blanchong et al, 2006;CWS and USFWS, 2007). A number of other studies have documented potentially harmful parasites in Whooping Cranes that can result from high waterbird densities, including from Sandhill Cranes (Grus canadensis), with which Whooping Cranes often forage during migration (Lu et al, 2013;Vogel et al, 2013;Bertram et al, 2017). Moreover, increasingly large groupings of Whooping Cranes present a potential mass mortality risk from extreme weather events like tornadoes and hail storms (Lingle, 1997;Higgins and Johnson, 1978;Narwade et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Krapu et al (2014) also noted that staging length in the CPRV was negatively correlated with arrival dates, suggesting that early arrivals tend to stay longer. A high number of Sandhill Cranes extending the period in which they stage at the CPRV will likely put additional pressure on agricultural foraging resources (Pearse et al 2010, Salvi 2012, as well as increase the disease risk for cranes and other waterbird species that overlap in wetland habitat use (Vogel et al 2013, Bertram et al 2017.…”
Section: Dependentmentioning
confidence: 99%
“…For instance, following conservation land purchases and restorations within segment 8 from 1998 to 2016, we found that meadow-prairie cover increased 12.1% but still totaled only 13.3% in 2016, which is well below the cover associated with segments 1 (20.7%) and 3 (49.6%) where Sandhill Crane use appears to be increasing most significantly (Tables 5,8). Further concentration of Sandhill Crane densities along the CPRV promotes a potential increase in disease risk for Sandhill Cranes and other organisms, including Whooping Cranes (Lu et al 2013, Bertram et al 2017, Fenton et al 2018. Additionally, increased densities of Sandhill Cranes in fewer reaches of the CPRV escalates the potential risk for mass mortality incidents resulting from extreme weather events like hail and ice storms (Higgins and Johnson 1978, Lingle 1997, Narwade et al 2014.…”
Section: Spatial Dynamicsmentioning
confidence: 99%